Cobalt oxyhydroxide nanoflakes enable ratiometric fluorescent assay of gallic acid - Chunlei Yang; Guiju Xu; Chenghao Hou; Hongwei Zhang (Food Chemistry: X)
Gallic acid (GA) is widely used in beverages, food, and other fields as antioxidant. However, GA is slightly toxic and the accumulation of GA is harmful to human body. Therefore, it's vital to develop simple and sensitive detection methods for GA. In this work, a novel ratiometric fluorescent nanoprobe (named CoOOH/OPD/SiNPs) for the GA detection in different foods was designed and prepared. The fluorescence of silicon nanoparticles (SiNPs) at 443 nm would be quenched by cobalt oxyhydroxide (CoOOH) nanoflakes. o-phenylenediamine (OPD) would be oxidized to 2,3-diaminophenazine (DAP) by CoOOH nanoflakes that have peroxidase-like activity, which produces a new fluorescent peak at 556 nm. Meanwhile, SiNPs' fluorescence would be quenched through DAP due to inner filter effect (IFE). With the addition of GA, the reductive decomposition of CoOOH decreased DAP level, causing IFE being restrained. The concentration of GA indicates an excellent linear relationship with fluorescence ratio (F443/F556) in range of 0.4–12 μM (R2 = 0.9937) with 0.16 μM detection limit. This nanoprobe is applied to GA detection in water, tea leaves, fruits and nut fruits, which would be expected to act as a portable device for complex substances analysis.